Effects of varying concentration of soybean oils on hemato-biochemical profile in mice - Salahuddin, M; Sarker, M; Ahmad, N; Miah, MA (Bangladesh Journal of Animal Science, 2013)
<!–[if gte mso 9]> <![endif]–><span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">Plant fat like soybean oil is believed to be less harmful to our body compared to animal fat. To know the effect of soybean oil on hemato-biochemical profile, a<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> total of 20, 6 weeks old <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">Swiss Albino<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> mice <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">were <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">randomly divided into 4 equal groups (n=5). Group A was considered as control fed <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">with rat pellets<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> and others were treated with 2% (group B), 4% (group C) and 8% (group D) soybean oil, respectively, in addition to <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">pellets<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">. <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">At the end of 45 days, hemato-biochemical parameters were analyzed. <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The total erythrocyte count<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;"> (TEC)<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> and hemoglobin<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;"> (Hb)<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> content were increased significantly (P<0.0<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">5<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">) in group C and D compared to control group A and the highest concentration was recorded in group D. The total serum cholesterol, triglycerides, HDL and uric acid were <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">also <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">increased significantly (p<0.01) in <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;">group C and D <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">compared to control and highest value was recorded in group D. It is concluded that some haemato-biochemical parameters of blood in the mice are affected by soybean oil enriched diet. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18502 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">): <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">148-151 <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>